Aquaporin 4 is a Ubiquitously Expressed Isoform in the Dogfish (Squalus acanthias) Shark - Cutler, Christopher P.; McIver, Bryce; Cramb, Gordon; Zeidel, Mark (Frontiers in Physiology, 2012)
The dogfish orthologue of aquaporin 4 (AQP4) was amplified from cDNA using degenerate PCR followed by cloning and sequencing. The complete coding region was then obtained using 5’ and 3’ RACE techniques. Alignment of the sequence with AQP4 amino acid sequences from other species showed that dogfish AQP4 has high levels (up to 65.3%) of homology with higher vertebrate sequences but lower levels of homology to agnathan (38.2%) or teleost (57.5%) fish sequences. Northern blotting indicated that the dogfish mRNA was approximately 3.2 kb and was highly expressed in the rectal gland (a shark fluid secretory organ). Semi-quantitative PCR further indicates that AQP4 is ubiquitous, being expressed in all tissues measured but at low levels in certain tissues, where the level in liver>gill> intestine. Manipulation of the external environmental salinity of groups of dogfish showed that when fish were acclimated in stages to 120% seawater (SW) or 75% SW, there was no change in AQP4 mRNA expression in either rectal gland, kidney or esophagus/cardiac stomach. Whereas quantitative PCR experiments using the RNA samples from the same experiment, showed a significant 63.1% lower abundance of gill AQP4 mRNA expression in 120% SW-acclimated dogfish. The function of dogfish AQP4 was also determined by measuring the effect of the AQP4 expression in Xenopus laevis oocytes. Dogfish AQP4 expressingoocytes, exhibited significantly increased osmotic water permeability (Pf) compared to controls, and this was invariant with pH. Permeability was not significantly reduced by treatment of oocytes with mercury chloride, as is also the case with AQP4 in other species. Similarly AQP4 expressing oocytes did not exhibit enhanced urea or glycerol permeability, which is also consistent with the water-selective property of AQP4 in other species.